AB0002 Genetic Variants in IL-17F, IL-23 and IL-23R in The Patients with Systemic Lupus Erythematosus. (15th July 2016) - Paradowska-Gorycka, A.; Sowinska, A.; Stypinska, B.; Grobelna, M.; Walczyk, M.; Olesinska, M.; Piotrowski, P.; Jagodzinski, P.P.
Abstract : Background: Systemic lupus erythematosus (SLE) is a severe multi-system autoimmune disease characterized by uncontrolled autoantibody formation, excessive proinflammatory cytokine production, tissue inflammation and damage to multiple organ systems. The IL-23-IL-17 axis, rather than the loop of IL-12 and IFN-c, have a central role in the autoimmune inflammation, and interaction between IL-23 and IL-17 is not only essential for the onset phase, but also for the destruction phase of SLE characterized by the T cell-mediated activation of osteoclastogenesis. Objectives: To investigate the potential association between IL-17F, IL-23 and IL-23R gene polymorphisms and SLE, we performed a case-control study based on Polish population. Methods: SLE patients and healthy individuals, were examined for IL-23A 703 G/A (rs11171806) and IL-23R (rs1884444 G/T, rs10489629 G/A) by TaqMan SNP genotyping assay, and for IL-17F 7488A/ G (rs763780) and 7383A /G (rs2397084) gene polymorphisms using the PCR– RFLP method. Results: An increased frequency of AG genotype as well as G allele of the IL-17F 7488 A/G (rs763780) was found in patients with SLE, as compared with healthy subjects (p=0.0007 and p=0.0012, respectively). Frequencies of the rs1884444 TT genotype and the rs1884444 T allele were also higher in SLE patients (both p<0.0001). Overall, very weak LD was observed between the IL-17F 7488A/ G (rs763780) and 7383A /G (rs2397084) polymorphisms (D'-0.003, r2 – 0.000). From four possible haplotypes, frequencies of one (AG) showed significant differences between both examined groups (p<0.0001). Moreover, we also observed a weak LD between the IL-23R rs10489629G/A and rs1884444 G/T (D'-0.199, r2 – 0.026). The genotype-phenotype analysis showed significant association between the IL-17F 7383 A/G (rs2397084) and mean value of the hemoglobin (p=0.01), between the IL-17F 7488 A/G (rs763780) and age (p=0.008) and lupus anticoagulant (p=0.09), between the IL-23 703 G/A (rs11171806) and urea (p=0.08) and C3 complement (p=0.03), and between the IL-23R rs1884444 G/T and activated partial thromboplastin time (p=0.06). Conclusions: Present findings indicated that IL-17F 7488 A/G (rs763780) and IL-23R rs1884444 G/T polymorphisms may be involved in susceptibility to SLE in the Polish population. References: Leng RX, Pan HF, Chen GM, Wang C, Qin WZ, Chen LL et al. IL-23: a promising therapeutic target for systemic lupus erythematosus. Arch Med Res. 2010; 41:221–225. Costa-Reis P, Sullivan KE. Genetics and epigenetics of systemic lupus erythematosus. Curr Rheumatol Rep. 2013; 15:369. McCarthy EM, Smith S, Lee RZ, Cunnane G, Doran MF, Donnelly S et al. The association of cytokines with disease activity and damage scores in systemic lupus erythematosus patients. Rheumatology 2014; 53:1586–1594. Acknowledgement: Supported by grant No 502–01–01124182–07474, Poznań University of Medical Sciences. The technical assistance of Mr. Agnieszka Hertel, Wieslawa Frankowska and Teresa Golaszewska is gratefully acknowledged. We are also grateful to all of the SLE patients whose cooperation made this study possible. Disclosure of Interest: None declared